Counterterrorism in the Philippines: Review of Key Issues - Mendoza, Ronald U (Archīum Ateneo, 2021)
Terrorism has taken root in almost all corners of the world with terrorist organizations thriving in both rich and poor countries. In the Philippines, the Human Security Act of 2007 came into force to address the threat of terrorism to the national security of the country. However, the law has never been fully utilized. To provide law enforcers with a stronger legal measure to address acts of terrorism in the country, President Duterte certified a new Anti-Terrorism Bill as urgent, with Congress adopting the Senate version and approving it in the shortest time possible. Despite opposition from various sectors and growing concerns over some of its provisions, President Duterte signed this into law, officially becoming Republic Act No. 11479 or the Anti-Terrorism Act of 2020. This article briefly reviews some key issues of counterterrorism measures in the Philippines.